PEMIKIRAN PENDIDIKAN HASAN LANGGULUNG TENTANG TUJUAN PENDIDIKAN DAN RELEVANSINYA DENGAN TUJUAN PENDIDIKAN - Samsuddin; Nur Shamsul, Mariyanto; Patahuddin, Askar; Jabar Idharudin, Abdul (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2024)
The aim of this research is to analyze and describe Hasan Langgulung's thoughts about the aims of Islamic education and its relevance to the aims of national education. This research uses qualitative methods descriptive with a type of literature study (library research) carried out through literature review and research. The primary data in this research is a book by Hasan Langgulung which was collected using documentation techniques and then reviewed, examined and discussed using the content analysis method which was carried out inductively. The findings and results of this research are, First, the objectives of Islamic education according to Hasan Langroll are (1) to produce students who are pious and have noble character who realize their devotion to Allah and realize their duties as caliphs (2) to create a pious society. Second, the aim of Islamic education in Hasan Langroll's thinking is relevant to the aim of national education, namely to produce students who are faithful, devout and have noble character and to produce students as good, democratic and responsible citizens.